Strategic performance measurement using balanced scorecard: A case of machine tool industry - Anil Kshatriya; Vijay Dharmadhikari; Deepak Srivastava; P. C. Basak (Foundations of Management, 2017)
This paper focuses on implementation, monitoring, and application of balanced scorecard (BSC) techniques in an organization involved in providing machine tool solutions to the industrial sector. The growth of the company considered in real time constituted improvements of both top and bottom lines. In the industry under consideration, it was observed that in our company, the top line was steadily growing but not the bottom line. This is when we started getting down to brass tacks and strategically focusing on growth in overall profits of the company. This included growing revenues by improving of EBITDA (earnings before interests, taxes, depreciation, and amortization) and by increasing efficiency (i.e., cutting costs). These improvements were implemented by chalking out a comprehensive BSC designed to suit the machine tool industry. The four perspectives of the management, namely, internal business process, organizational learning, financial perspective, and customer perspective, have been considered lucidly and enunciate the parameters that affect the BSC very aptly. The BSC designed considered 9 objectives and 27 relative measures of these factors to quantify the various quantitative and qualitative dimensions that affect the company's performance. A Balanced Lean Index (BL Score) was used to measure the results for company X.
Keywords: 650; balanced lean index; balanced scorecard; internal business process; organizational learning; financial perspective and strategy